Resistance To Change And Erp Implementation Success: The Moderating Role Of Change Management Initiatives - U. Ahmed, Zafar; Zbib, Imad; Arokiasamy, Sawaridass; T. Ramayah, T. Ramayah; Lo , May Chiun (Asian Academy of Management (AAM), 2006)
Enterprise Resource Planning (ERP) is a useful tool that builds strong capabilities, improves performance, supports better decision making, and provides competitive advantage for businesses. ERP aims to help the management by setting better business practices and equipping them with the right information to take timely decision. In any new technology implementation, one of the issues that need to be addressed is the resistance to change. Many implementations have failed due to strong resistance from the end users. Thus, the main purpose of this paper is to test the impact of resistance to change on ERP's implementation success and how change management initiatives acts in the capacity of a moderating role. Using data collected from 69 manufacturing organizations through a mail survey, it was found that resistance to change is negatively related to achievement of predetermined goals (b = –0.930, p < 0.01) and user satisfaction (b = –0.952, p < 0.01). Further, change management initiatives did not moderate the relationship between resistance and predetermined goals but it moderated the relationship between resistance and user satisfaction. In addition, change management initiatives have a direct positive impact on user satisfaction. This research concludes that the human factor is very important in ERP's implementation.